The Curious Case of Brazil's Closedness to Trade - Canuto, Otaviano; Fleischhaker, Cornelius; Schellekens, Philip (World Bank, Washington, DC, 2015)
Although Brazil has become one of the largest economies in the world, it remains among the most closed economies as measured by the share of exports and imports in gross domestic product. This feature cannot be explained simply by the size of Brazils economy. Rather, it is due to an economic structure reliant on domestic value chain integration as opposed to participation in global production networking. It also reflects more generally an export base that shows lack of dynamism. Opening up and moving toward integration into global value chains could produce efficiency gains and help Brazil address its productivity and competitiveness challenges.